Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera) IV: New additions of Chinese Furcilarnaca Gorochov, 2004 - Liu, Jing; Wu, Xiangyi; Bian, Xun (Zootaxa, 2022)
Based on the specimens from Guangxi and Yunnan deposited in the Guangxi Normal University, the paper is firstly reported the female sex of two known species from China, viz. Furcilarnaca armata (Bey-Bienko, 1957) and Furcilarnaca forceps (Bey-Bienko, 1962). The female of Furcilarnaca armata (Bey-Bienko, 1957) is very similar to Furcilarnaca chiangdao in seventh abdominal tergite and subgenital plate, and they may belong to the same species. After examining the female subgenital plate of Furcilarnaca chirurga (Bey-Bienko, 1962), we treat Furcilarnaca hirta as a valid species. Mitochondrial genomes of six specimens of three Furcilarnaca species were sequenced and annotated in this study. The organization and gene content of new sequenced mitogenomes were conserved, except for significant variation of the control region. All the PCGs started with the typical ATN codons and most ended with complete TAA or TAG codons. Combined with five mitogenomes in NCBI, a total of twelve specimens (including one outgroup) were used in phylogenetic analysis based on 13 PCGs. The result revealed that Furcilarnaca was a monophyletic group. These data will provide more meaningful genetic information and validate the phylogenetic relationships within the Gryllacrididae.